Cycle stability of La-Mg-Ni based hydrogen storage alloys in a gas–solid reaction. (14th September 2017) - Lim, Kean Long; Liu, Yongning; Zhang, Qing-An; Lin, Kuen-Song; Chan, Sammy Lap Ip
Abstract: The cycle stability of La-Mg-Ni based alloys in a gas–solid reaction system was investigated in this work. Both partial substitutions of La and Ni by Ce and Al, respectively, improved the cycle stability of La(0.65−x) Cex Ca1.03 Mg1.32 Ni(9−y) Aly alloys. Although the addition of Al reduced the hydrogen storage capacity significantly, it is still important to be included in the system for its superior property in improving the cycle life. Hence, two optimized samples with a small addition of Al (y = 0.10) were used to compare with the cycle life of CaNi5 . It was found that the Ce and Al added samples have a better hydrogen capacity retention than that of samples without element substitution; and their overall hydrogen storage capacity was still higher than that of CaNi5 . We also found that heat treatment used in this study did not fully recover the hydrogen storage capability of La-Mg-Ni based alloy to its original storage capacity. A probable reason was the heat treatment used in this study could only recover the degradation caused by the disproportionation to some extent, but the treatment was unable to reverse the degradation caused by decrepitation. Highlights: Effects of partial substitutions of La and Ni with Ce and Al were studied. Both Ce and Al improved the cycle life of La-Mg-Ni based alloys. Addition of Al produced non-hydrogen absorbing phase. Al addition reduced the overall hydrogen storage capacity but improved cycle life.